Ovitrap surveillance as dengue epidemic predictor - Pessanha, José Eduardo Marques; Brandão, Silvana Tecles; Almeida, Maria Cristina Mattos; Cunha, Maria da Consolação Magalhães; Sonoda, Ivan Vieira; Bessa, Adelaide Maria; Nascimento, José Carlos (Journal of Health & Biological Sciences, 2014)
We used ovitraps, set out each two week to monitor for Aedes spp. at Belo Horizonte City, Brazil, 2002-2013. The average proportion of ovitraps with mosquitoes – the ovitraps index (OIP) had flutuations in these years. The average egg number of Aedes sp. (MNE) revealed that is a good sensitive index for detecting the presence of Aedes than the Breteau index. They also showed that Ae aegypti was a dominant species in studies periods. Analyses revealed that monthly cases of Dengue fever (DF) and Dengue hemorrhagic fever (DHF) were correlated with the number of adult female Aedes spp. collected in all the years with the correlation coefficient of0.54 in 2002-2013. Our survey also indicated that air temperature and precipitation are directly related to increases of mosquitoes in ovitraps. Thus, under circumstances where the Breteau index is low, the ovitrap method should be applied as an good and opportune surveillance tool to evaluate the risk of human dengue infection, and the need scaling up for mosquito vector control.